2021
DOI: 10.3390/medicina57101082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 Pandemic on Working Conditions of Dentists in Poland and Turkey

Abstract: Background and Objectives: Due to the specific working conditions dental professionals represent a group of high risk of infection and COVID-19 pandemic in many ways have influenced their working environment. The aim of this study was to evaluate effects of COVID-19 pandemic on working conditions of dentists in Poland and Turkey. Materials and Methods: The study was an anonymous online questionnaire conducted among thedentists in two countries: Poland and Turkey. The survey consisted of general questions, COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
2
0
2
Order By: Relevance
“…Safety goggles, already being used in many dental offices, showed slightly increased use in all practices. A similar positive trend in the usage of FFP2/3 masks or goggles could also be identified in studies from Poland, Turkey and Italy [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 75%
“…Safety goggles, already being used in many dental offices, showed slightly increased use in all practices. A similar positive trend in the usage of FFP2/3 masks or goggles could also be identified in studies from Poland, Turkey and Italy [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 75%
“…A study in Iranian dentists showed that 57% could face financial problems in the future [4]. Similarly, in studies carried out in Poland, Turkey, and Romania, a significant decrease in the income of dentists was found during the pandemic [35,37].…”
Section: Possible Explanations For the Study Findingsmentioning
confidence: 96%
“…13 Although dentists do take extra personal protective measures while performing dental procedures, studies show that 16-24% of dentists working in Turkey have been infected with SARS-CoV-2. [14][15][16] Due to the cross-contamination caused by aerosols, dental professionals are anxious about being infected and transmitting the infection to their families and friends, which may affect their behavior and make them experience a sense of fear and anxiety. 17 Research has shown that 2.6% of dentists, 18 5.1% of healthcare professionals 19 and 3.5% of medical students 20 received psychological support during the pandemic.…”
Section: Introductionmentioning
confidence: 99%